Marital Satisfaction Based on Father Involvement in Parenting, Problem-Solving Skills, and Cognitive Emotion Regulation through Emotional Empathy in Mothers of Children with Cerebral Palsy - Farahbakhsh Daghigh, Matin; Homai, Rezvan; Jayrvand, Hamdallah (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to investigate marital satisfaction based on father involvement in parenting, problem-solving skills, and cognitive emotion regulation through emotional empathy in mothers of children with cerebral palsy.Methods: The research design was descriptive-survey and used a structural equations approach. The statistical population included 148 mothers of children with cerebral palsy in the city of Rasht in 2022. Using a census and purposive sampling method, all 148 individuals were selected as the sample. Data were collected using the ENRICH Marital Satisfaction Questionnaire, Alabama Parenting Test (Parent Form), Family Problem-Solving Questionnaire, Emotion Regulation Questionnaire, and Emotional Empathy Questionnaire. Data analysis was performed using SPSS (version 28) and Lisrel (version 10).Findings: The findings showed a direct relationship between father involvement in parenting, problem-solving skills, cognitive emotion regulation, and emotional empathy with marital satisfaction (p ≤ .01). An indirect relationship was also found between father involvement in parenting, problem-solving skills, and cognitive emotion regulation through the mediation of emotional empathy with marital satisfaction (p ≤ .01).Conclusion: To alleviate or reduce the burden on mothers of children with cerebral palsy, fathers must actively participate in parenting. This collaboration enables both parents to solve problems and control negative emotions while supporting each other with a high level of emotional empathy, thereby fostering and enhancing marital satisfaction.